THE EFFECTIVENESS OF SEMA NO. 3 OF 2023 IN REDUCING DIVORCE RATES: A SOCIO-LEGAL STUDY AT THE KRAKSAAN RELIGIOUS COURT - Shofiatul Jannah; Dzulfikar Rodafi; Salsabillah Jannah Zhika Prameswari; Aprilia Intan Jannah Pratiwi; Imamuddin Imamuddin (JURNAL HAKAM, 2026)
This study examines the effectiveness of the implementation of Supreme Court Circular Letter (SEMA) No. 3 of 2023 in reducing divorce rates at the Kraksaan Religious Court, Indonesia, using a socio-legal approach. The regulation introduces a six-month separation requirement for divorce based on disputes, aiming to prevent impulsive divorce and strengthen family resilience. This research employs empirical legal methods with data collected through interviews, court documents, and statistical records. The findings reveal a paradox: despite the formal implementation of SEMA, divorce cases increased significantly after its enactment. This indicates that the policy operates more as a procedural filter than as an effective instrument of social control. Using Soerjono Soekanto’s theory of legal effectiveness and Edward III’s implementation framework, the study shows that the main limitations lie not in legal substance or institutional capacity, but in socio-cultural factors, including low public legal awareness, limited policy socialization, weak evidentiary mechanisms, and the normalization of divorce in society. Consequently, the regulation fails to substantially influence litigant behavior. This study argues that legal policy alone is insufficient to address complex social issues such as divorce. A more holistic approach integrating legal regulation with public education, improved mediation, and socio-cultural engagement is required to enhance policy effectiveness. The research contributes to socio-legal scholarship by highlighting the gap between normative legal design and empirical reality in judicial policy implementation.